2014
DOI: 10.1111/1365-2435.12256
|View full text |Cite
|
Sign up to set email alerts
|

Variation in elemental stoichiometry and RNA:DNA in four phyla of benthic organisms from coral reefs

Abstract: Summary The elemental composition of organisms has been linked to traits such as growth rates, through investment of phosphorus (P) in RNA (called the Growth Rate Hypothesis) and through ecological processes such as susceptibility to predation and herbivory. To test the predictions of the Growth Rate Hypothesis, we assessed the elemental composition and RNA of four phyla of common, co‐occurring benthic coral reef organisms, corals, and green, brown and red macroalgae, whose patterns of dominance are predicte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…Recent evidence supports the BN hypothesis (Peñuelas et al, 2011(Peñuelas et al, , 2019a across organisms and ecosystems in plant (Sardans and Peñuelas, 2014b;Sardans et al, , 2016aUrbina et al, 2015Urbina et al, , 2017de la Riva et al, 2017;Castellanos et al, 2018;Hu et al, 2018;Reimann et al, 2018;Zhao et al, 2018a), animal (Bartrons et al, 2018;Gonzalez et al, 2018) and microbial communities (Pereira and Berry, 2017) (Figure 4). Foliar elemental composition and stoichiometry are more similar in phylogenetically close species than in distantly related species (Sardans and Peñuelas, 2014b;Sardans et al, , 2016bSardans et al, , 2019, as indicated by studies that have reported the dependence of plant and animal taxonomy and/or phylogeny on organ or body stoichiometry (Zhang et al, 2012;Lovelock et al, 2014;Yang et al, 2015;de la Riva et al, 2017;Wu et al, 2017;Castellanos et al, 2018;Hu et al, 2018;Reimann et al, 2018;Zhao et al, 2018a;Zhang et al, 2019c). Some studies have reported no links between phylogeny and N:P ratios (Sun et al, 2017a), whereas > 90% of recent studies have reported a significant correlation between species elemental composition and taxonomic/phylogenetic distance (Table 2).…”
Section: Biogeochemical Stoichiometrymentioning
confidence: 95%
“…Recent evidence supports the BN hypothesis (Peñuelas et al, 2011(Peñuelas et al, , 2019a across organisms and ecosystems in plant (Sardans and Peñuelas, 2014b;Sardans et al, , 2016aUrbina et al, 2015Urbina et al, , 2017de la Riva et al, 2017;Castellanos et al, 2018;Hu et al, 2018;Reimann et al, 2018;Zhao et al, 2018a), animal (Bartrons et al, 2018;Gonzalez et al, 2018) and microbial communities (Pereira and Berry, 2017) (Figure 4). Foliar elemental composition and stoichiometry are more similar in phylogenetically close species than in distantly related species (Sardans and Peñuelas, 2014b;Sardans et al, , 2016bSardans et al, , 2019, as indicated by studies that have reported the dependence of plant and animal taxonomy and/or phylogeny on organ or body stoichiometry (Zhang et al, 2012;Lovelock et al, 2014;Yang et al, 2015;de la Riva et al, 2017;Wu et al, 2017;Castellanos et al, 2018;Hu et al, 2018;Reimann et al, 2018;Zhao et al, 2018a;Zhang et al, 2019c). Some studies have reported no links between phylogeny and N:P ratios (Sun et al, 2017a), whereas > 90% of recent studies have reported a significant correlation between species elemental composition and taxonomic/phylogenetic distance (Table 2).…”
Section: Biogeochemical Stoichiometrymentioning
confidence: 95%
“…The relative quantities of RNA and DNA were determined by a fluorescence assay using 2,7-diamino-10-ethyl-9-phenylphenanthridinium bromide (ethidium bromide [EtBr]) as described in Reef et al (2010) and Lovelock et al (2014). Briefly, EtBr binds specifically to double-stranded polynucleotides and while doing so emits a yellow fluorescence when irradiated with ultra violet radiation.…”
Section: Dna and Rna Determinationmentioning
confidence: 99%
“…As the extraction efficiency of the nucleic acids was not known, we conservatively present the data as RNA : DNA ratio, assuming that if cells were broken then both RNA and DNA were released into the extraction buffer. The RNA : DNA ratio and concentration of RNA in tissues were significantly correlated (Lovelock et al 2014). Thus, we consider the ratio of RNA : DNA to be indicative of the concentration of RNA in tissues, although the extraction efficiency is not known and is likely to vary among taxa.…”
Section: Dna and Rna Determinationmentioning
confidence: 99%
“…Therefore, imbalanced DIN:DIP ratios can induce significant changes in the stoichiometry (Carbon (C):N:P) of coral tissue, itself dependent on DIN and DIP availability in seawater, as observed in phytoplankton [ 34 , 35 ]. Because P is essential for ribosomal RNA and N is a major component of nucleic acids and proteins, coral growth and health are directly related to tissue N and P content [ 36 , 37 ]. Measuring the elemental stoichiometry of coral tissues and symbionts may therefore be used to determine nutrient limitation and assess how the seawater DIN:DIP ratio might alter coral physiology.…”
Section: Introductionmentioning
confidence: 99%